PENGARUH FRAUD PENTAGON TERHADAP FRAUDULENT FINANCIAL REPORTING - Muhammad Syauqi (2020)
This research is a quantitative study that aims to determine the effect of fraud pentagon on the possibility of fraudulent financial reporting. Fraud Pentagon theory is measured by pressure (financial target), opportunity (ineffective monitoring), rationalization (change in auditor), competence (change of director), and arrogance (frequent number of CEO's picture). The method used in this research is purposive sampling. The sample consisted of 20 companies from 107 state-owned companies used as this research population in the period of 2014 - 2018. Data were analyzed using logistic regression and descriptive statistical analysis with the help of data processing application using SPSS (Statistical Product and Service Solution) 25th. The results of this study showed that the financial target, ineffective monitoring, change in auditor, change of director, and frequent number of CEO's picture variables have no effect towards the fraudulent financial reporting.